Complementary Therapies in Allergic Rhinitis. (13th November 2013) - Sayin, Ibrahim; Cingi, Cemal; Oghan, Fatih; Baykal, Bahadir; Ulusoy, Seckin
Abstract : Objective . To determine the prevalence of herbal treatment of allergic rhinitis. Methods . In this prospective study, patients who were diagnosed with perennial allergic rhinitis were questioned about their use of natural products/herbal therapies for their symptoms. Results . In total, 230 patients were enrolled. Overall, 37.3% of the patients stated that they had used natural products/herbal therapies at least once. Women were more likely than men to use herbal supplements (38.3% versus 32.4%). Ten different types of herbal supplements were identified, with stinging nettle ( Urtica dioicath ), black elderberry ( Sambucus nigra ), and Spirulina being the most common (12.6%, 6.1%, and 5.7%, resp.). Conclusion . This study found a high prevalence of herbal treatment usage for the relief of allergic rhinitis symptoms in Turkey. The herbal products identified in this study and in the literature are discussed.